Perchlorate on Mars: a chemical hazard and a resource for humans. Issue 4 (12th June 2013) - Davila, Alfonso F.; Willson, David; Coates, John D.; McKay, Christopher P.
Abstract: Perchlorate (ClO4 − ) is widespread in Martian soils at concentrations between 0.5 and 1%. At such concentrations, perchlorate could be an important source of oxygen, but it could also become a critical chemical hazard to astronauts. In this paper, we review the dual implications of ClO4 − on Mars, and propose a biochemical approach for removal of perchlorate from Martian soil that would be energetically cheap, environmentally friendly and could be used to obtain oxygen both for human consumption and to fuel surface operations.